2016
DOI: 10.1089/nat.2015.0576
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Method for Profiling Protein Interactions with LNA-Modified Antisense Oligonucleotides Using Protein Microarrays

Abstract: Development of locked nucleic acid (LNA) gapmers, antisense oligonucleotides used for efficient inhibition of target RNA expression, is limited by nontarget-mediated hepatotoxicity. Increased binding of hepatocellular proteins to toxic LNA gapmers may be one of the mechanisms contributing to LNA gapmer-induced hepatotoxicity in vivo. In the present study, we investigated the protein binding propensity of nontoxic sequence-1 (NTS-1), toxic sequence-2 (TS-2), and severely highly toxic sequence-3 (HTS-3) LNA gapm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 12 publications
1
13
0
Order By: Relevance
“…While generally well tolerated, these single-stranded oligonucleotides (ONs) that hybridize with cellular RNA targets sometimes are associated with clinical adverse effects including hepatotoxicity, kidney tubular toxicity or pro-inflammatory effects (injection site reactions and flu-like symptoms) [ 1 6 ]. The mechanism of these adverse effects is not fully understood, but mechanisms involving hybridization to off-target RNA sequences [ 2 ] or aptameric binding to proteins [ 7 , 8 ] have been shown to be contributing factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While generally well tolerated, these single-stranded oligonucleotides (ONs) that hybridize with cellular RNA targets sometimes are associated with clinical adverse effects including hepatotoxicity, kidney tubular toxicity or pro-inflammatory effects (injection site reactions and flu-like symptoms) [ 1 6 ]. The mechanism of these adverse effects is not fully understood, but mechanisms involving hybridization to off-target RNA sequences [ 2 ] or aptameric binding to proteins [ 7 , 8 ] have been shown to be contributing factors.…”
Section: Introductionmentioning
confidence: 99%
“…Due to their polyanionic nature, PS ONs have a moderate to high binding affinity to various proteins including serum proteins, heparin-binding molecules and several growth factors [ 7 , 16 ]. New generation ONs are not only PS-modified but also contain building blocks with sugar modifications at the 2’-position including 2’-O-methyl (2’OMe), 2’-O-methoxyethyl (MOE), locked nucleic acid (LNA) or constrained ethyl (cEt) substitutions.…”
Section: Introductionmentioning
confidence: 99%
“…However, such processes are poorly understood and are likely to be caused by a combination of (a) hybridization-dependent off-target toxicity due to hybridization of the respective ASO to non-intended RNA targets because of sequence similarity 1 , 11 and (b) hybridization-independent toxicity caused by binding of the ASO to intracellular proteins, thereby interfering with their function and, ultimately, leading to toxicity. 12 , 13 We have previously shown that a more exhaustive OTE assessment, utilizing both in silico predictions and in vitro confirmation in relevant cell lines, is a crucial aspect of ASO drug optimization. 11 Importantly, with RNase H1 activity residing predominantly within the nucleus, ASOs are as likely to interact with intronic sequences as with exonic regions, leading to a considerable number of interactions with primary RNAs.…”
Section: Introductionmentioning
confidence: 99%
“…Cell uptake, intracellular trafficking, and localization may differ across AON molecules and explain some of the observed diversity. Similar to putative mechanisms in the liver, AONs may interact with critical intracellular proteins to disrupt their function 8 or may hybridize to unintended transcripts with a detrimental impact on pathways involved with cell maintenance 9, 10. The lack of in vitro models that mimic the in vivo toxicity of AONs has considerably limited the mechanistic understanding of the effect of these compounds at a cellular level.…”
Section: Introductionmentioning
confidence: 99%